تنفيذ المنهج المستقل قائم على نظام الائتمان الفصلي - Ulloh, Faidhul Mahdhi Ala' (Maliki Interdisciplinary Journal, 2024)
This research aims to (1) find out how the independent curriculum is implemented, (2) students' responses to the independent curriculum, (3) apart from that, the obstacles and challenges faced by implementing the independent curriculum in the first Islamic society. secondary school in Blitar. This research is a type of qualitative research. The research topic is aimed at class 10 students class of 2022 at Islamic Senior High School 1 Blitar who use the Independent Observation curriculum in the teaching and learning process. The data collection technique was carried out by interviewing several grade 10 students, several teachers, and the school's vice president for curriculum. The results of this research are that Islamic Senior High School 1 Blitar applies several parts and principles of an independent curriculum, because the school here implements a semester credit system, no longer using student worksheets (LKS) as teaching materials. How to implement an independent curriculum includes flexibility in material selection, learning-based projects, differentiated teaching methods, and competency-based assessments. Answers Students vary in their responses. Most students consider this independent curriculum to be physically and mentally taxing, because there are many and important assignments not just one in one day, but sometimes all subjects like that. The school itself is still facing many obstacles in its implementation, namely that this curriculum is something new, teacher preparation is not yet ready, and the implementation of the planned projects is not yet ready.